Politik Kekerabatan pada Pilkada 2020 di Jawa Tengah: Aktor-aktor yang Terlibat dan Pengaruhnya: The Actors Involved and Their Influences - Diniyanto Ayon; Dani Muhtada; Aji Sofanudin (Ministry of Home Affairs, 2021)
Kinship politics in the 2020 Pilkada in Central Java occurred in 11 out of 21 regions that held Pilkada. This number indicates that more than half of the regions in Central Java are exposed to kinship politics in the 2020 Pilkada. This condition would not have happened without the actors involved. The role of actors in constructing kinship politics is something that is difficult to deny. Therefore, this research is important to find actors involved in kinship politics in the 2020 Pilkada in Central Java. The fundamental question that is important to ask is who is involved in kinship politics in the 2020 Pilkada in Central Java? How do these actors influence the 2020 Pilkada contest in Central Java? The purpose of this research is to find the formulation of the problem. This article shows three actors who play a role in constructing kinship politics in Central Java, namely (1) the main actor; (2) relative actor; and (3) other actors. The influence of these three actors can be classified into large, medium, and small influences. This article shows that these three actors have varied and inconsistent effects. This article concludes that kinship politics is not a guarantee for a candidate to win local political contestation.